Facilitating the Development of a Topical and Functional Syllabus for Junior High School English Club : Memfasilitasi Pengembangan Silabus Topikal dan Fungsional untuk Klub Bahasa Inggris di Sekolah Menengah Pertama - Isnaniah, Isnaniah; Hamid, Syifa Fadhilah; Shopia, Khilda (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
In late 2021, an Extracurricular English Club was established at SMP Garuda, Kota Tangerang, following mentoring and workshops conducted by the Community Service Team from the English Education Department of Universitas Islam Syekh-Yusuf. After operating for a year, the school identified several areas for improvement and evaluation regarding the implementation of the club's activities, particularly concerning the extracurricular coaches and the content delivered to students. This prompted the school to plan the development of a structured curriculum or guidebook for the English Club at SMP Garuda. To enhance the quality of the English Club's extracurricular activities, a community service program was initiated to assist in the development of the club's curriculum at SMP Garuda Kota Tangerang. Although the English Club is an extracurricular program, it is essential to establish a clear set of activities, such as a syllabus and relevant materials, to help students achieve the desired outcomes in improving their English language skills. Through this program, facilitators provided guidance in developing a syllabus-based curriculum focused on topical and functional content. This was accomplished by conducting a Needs Analysis and a Focus Group Discussion (FGD) with the coaches of the English Club at SMP Garuda Kota Tangerang.